Reporting of thyroid fine needle aspiration cytology with the use of the Bethesda System (TBS) of 150 cases - Patel, Mandakini M.; Patel, Mubim I.; Gamit, Bhavna G.; Patel, Sharmistha M. (International Journal of Research in Medical Sciences, 2018)
Background: Fine needle aspiration cytology (FNAC) is very simple, rapid, cost effective diagnostic test to evaluate thyroid swelling. The Bethesda system for reporting thyroid cytopathology gives guidelines which remains the same while reporting the thyroid FNAC. There are six diagnostic categories of lesions: (I) Non-diagnostic/Unsatisfactory, (II) Benign, (III) Atypical follicular lesion of undetermined significance (AFLUS), (IV) Suspicious for follicular neoplasm (SFN), (V) Suspicious for malignancy (SM), (VI) Malignant. Methods: The study was carried out in Department of Pathology, Government Medical College affiliated with a Government hospital, Gujarat. It includes 150 patients, coming to the outpatient departments with a complaint of thyroid swelling from January 2017 to December 2017. The patients age ranges from 7 years to 75 years (Male-20, Female-130). The procedure was done with the patient in a supine position without a pillow. Patients were instructed not to speak or swallow during the procedure to avoid movement of the gland. The reporting was done with the current Bethesda nomenclature. Results: There were 150 cases of thyroid FNAC, 3 cases (2 %) were non-diagnostic (TBS-I), 133 cases (88.7 %) were benign (TBS-II), 6 cases (4 %) were atypical follicular lesion of undetermined significance (AFLUS) (TBS-III), 5 cases (3.4 %) were suspicious for follicular neoplasm (TBS-IV), 2 cases (1.3 %) were suspicious for malignancy (TBS-V), and 1 case (0.6 %) was malignancy (TBS-VI). Conclusions: The Bethesda system is very useful standardized system for reporting thyroid cytopathology, improving communication between cyto-pathologists and clinicians, inter-laboratory agreement, leading to more consistent management approaches.